PERAN KEPUTUSAN PEMBELIAN DALAM MEMEDIASI LIFESTYLE E-WOM DAN PRODUCT DIVERSITY TERHADAP KEPUASAN KONSUMEN CONATO BAKERY & CAFÉ SITUBONDO - Hafi, Mufida Asri Laila; Praja, Yudha; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The era of increasingly competitive business competition requires a deep understanding of consumer behavior as a strategic factor in designing and implementing practical and sustainable marketing strategies. Consumer preferences constantly change, and business actors must constantly adapt and innovate to meet consumers’ needs, desires, and expectations. This study aims to analyze and test the role of purchasing decisions in mediating lifestyle, E-WOM, and product diversity on customer satisfaction at Conato Bakery & Café Situbondo. The sampling technique was determined by purposive sampling. This study’s data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that lifestyle has a negative but not significant influence on purchasing decisions, E-WOM has a significant positive influence on purchasing decisions, Product Diversity has a significant positive influence on purchasing decisions, lifestyle has a negative but not significant influence on consumer satisfaction, E-WOM has a significant positive influence on consumer satisfaction, Product diversity has a negative but not significant influence on consumer satisfaction, Purchasing decisions have a significant positive influence on consumer satisfaction. The indirect influence hypothesis test results show that lifestyle has a negative but insignificant influence on consumer satisfaction through purchasing decisions, E-WOM has a significant positive influence on consumer satisfaction through purchasing decisions, and Product diversity has a significant positive influence on consumer satisfaction through purchasing decisions.